The Effect of STAD Learning Model On The Motivation And Social Studies Knowledge In Junior High School - Muhamad Miftahul Alim; Ketut Prasetyo; Sunarto Sunarto (The Indonesian Journal of Social Studies, 2019)
This study aims to determine the consistent changes of students' learning motivation resulting from the learning process using the STAD learning model and its effect on student learning outcomes. This study was the pretest-posttest control group design. Sample in this study was VIII class who were randomly determined. The data obtained then tested different using independent sample t-test. The results showed that the two research classes experienced a positive change in the motivation and learning outcomes of students. In the experimental class with STAD learning model showed motivation and learning outcomes that were better than class control. The post-test calculation shows that learners' motivation with the Sig. (2-tailed) 0.003, where 0.003 <0.05 means that there are significant differences. Learning outcomes that show the value of Sig. (2-tailed) 0,000, where 0,000 <0,05 means that there are significant differences between the experimental and control classes. The existence of significant differences indicates that there is an effect of the STAD learning model on students' motivation and learning outcomes.